Association of Medicaid Expansion With Rates of Utilization of Cardiovascular Therapies Among Medicaid Beneficiaries Between 2011 and 2018. Issue 1 (January 2021) - Sumarsono, Andrew; Lalani, Hussain; Segar, Matthew W.; Rao, Shreya; Vaduganathan, Muthiah; Wadhera, Rishi K.; Das, Sandeep R.; Navar, Ann Marie; Fonarow, Gregg C.; Pandey, Ambarish
Abstract : Background: The Affordable Care Act expanded Medicaid eligibility allowing low-income individuals greater access to health care. However, the uptake of state Medicaid expansion has been variable. It remains unclear how the Medicaid expansion was associated with the temporal trends in use of evidence-based cardiovascular drugs. Methods: We used the publicly available Medicaid Drug Utilization and Current Population Survey to extract filled prescription rates per 1000 Medicaid beneficiaries of statins, antihypertensives, P2Y12 inhibitors, and direct oral anticoagulants. We defined expander states as those who expanded Medicaid on or before January 1, 2014, and nonexpander states as those who had not expanded by December 31, 2018. Difference-in-differences (DID) analyses were performed to compare the association of the Medicaid expansion with per-capita cardiovascular drug prescription rates in expander versus nonexpander states. Results: Between 2011 and 2018, the total number of prescriptions among all Medicaid beneficiaries increased, with gains of 89.7% in statins (11.0 to 20.8 million), 76% in antihypertensives (35.3 to 62.2 million), and 37% in P2Y12 inhibitors (1.7 to 2.3 million). Medicaid expansion was associated with significantly greater increases in quarterly prescriptions (per 1000 Medicaid beneficiaries) of statins (DID estimate [95% CI]: 22.5 [16.5–28.6], P <0.001), antihypertensives (DID estimate [95% CI]: 63.2 [47.3–79.1], P <0.001), and P2Y12 inhibitors (DID estimate [95% CI]: 1.7 [1.2–2.2], P <0.001). Between 2013 and 2018, >75% of the expander states had increases in prescription rates of both statins and antihypertensives. In contrast, 44% of nonexpander states saw declines in statins and antihypertensives. The Medicaid expansion was not associated with higher direct oral anticoagulants prescription rates (DID estimate [95% CI] 0.9 [−0.3 to 2.1], P =0.142). Conclusions: The 2014 Medicaid expansion was associated with a significant increase in per-capita utilization of cardiovascular prescription drugs among Medicaid beneficiaries. These gains in utilization may contribute to long-term cardiovascular benefits to lower-income and previously underinsured populations.